Examining Spillover Effects From Teach For America Corps Members in Miami-Dade County Public Schools. (November 2019) - Backes, Ben; Hansen, Michael; Xu, Zeyu; Brady, Victoria
This article examines Teach For America's (TFA) placement strategy in Miami-Dade County Public Schools, in which large numbers of TFA corps members are placed as clusters into a targeted set of disadvantaged schools, to investigate whether the large-scale infusion of TFA corps members into these schools induced broader improvements across the school. Using 6 years of administrative data from the district, we exploit variation in TFA density over time within schools to measure the extent to which increases in density were associated with improvements in student test scores. We find that many of the schools chosen to participate in the cluster strategy experienced large subsequent gains in mathematics achievement. These gains were driven in part by the direct effect of having larger numbers of classrooms staffed by effective TFA teachers. However, we do not find any evidence that the clustering strategy led to any spillovers on schoolwide performance.